UTILIZATION OF LEARNING FACILITIES: AN EFFORT TO IMPROVE THE PERFORMANCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS - Murni Murni (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Education is the main factor in the formation of the whole human person. Education plays an important role in shaping the good or bad of the human person according to normative standards. Realizing this, the government is very serious in dealing with the field of education, because with a good education system it is hoped that the next generation of quality will emerge and be able to adapt to live in society, nation and state. Management is one of the most important human activities, which has the main task of designing and maintaining an environment, where people work together in groups, so as to achieve common goals. In other words, a manager has the burden of responsibility for taking actions that will enable people to make their best contribution to the group's goals. Meanwhile, Islamic culture in schools is actually a school culture built on Islamic values, or in other words, a school culture that contains Islamic values. Islamic culture in schools is actually an effort to realize Islamic values as a tradition in behavior that is followed by all school members.